Foreign Divestment – Crisis or Chance for China's Innovation Edge? - Guopei Fang; Holger Görg; Aoife Hanley; Haiou Mao (China & World Economy, 2022)
The recent move towards decoupling from China, prompted by the 2018 trade conflict, has implications for the innovativeness of Chinese firms. Using patent data from the Chinese State Intellectual Property Office, together with comprehensive firm-level data, and applying an inverse propensity score reweighting methodology to deal with selection bias, we estimated changes in the patenting activity of firms following ownership transition to Chinese owners, linking these changes to the differential taxation incentives offered to foreign investors. Far from crippling innovation, divestment has sparked an increase in patent applications – including higher end invention patents – and other innovation measures. Together with robustness checks, our estimations suggest a real improvement in innovation rather than just a window-dressing exercise. We suggest that one possible explanation may be an effort by the new Chinese owners to reduce their tax burden. Our supplementary findings on tax payments and subsidy receipts following divestment appear in line with this interpretation.
Keywords: 330; China; foreign divestment; innovation; patents; research and development